Chronic low-level Pb exposure during development decreases the expression of the voltage dependent anion channel in auditory neurons of the brainstem - Prins, John M. (2010)
Lead (Pb) exposure is a risk factor for neurological dysfunction. How Pb produces these behavioral deficits is unknown, but Pb exposure during development is associated with auditory temporal processing deficits in both humans and animals. Pb disrupts cellular energy metabolism and efficient energy production is crucial for auditory neurons to maintain high rates of synaptic activity. The voltage dependent anion channel (VDAC) is involved in the regulation of mitochondrial physiology and is a critical component in controlling mitochondrial energy production. We have previously demonstrated that VDAC is an in-vitro target for Pb, therefore, VDAC may represent a potential target for Pb in the auditory system. In order to determine whether Pb alters VDAC expression in central auditory neurons, CBA/CaJ mice (n=3–5/group) were exposed to 0.01 mM, or 0.1 mM Pb acetate during development via drinking water. At P21, immunohistochemistry reveals a significant decrease for VDAC in neurons of the Medial Nucleus of the Trapezoid Body. Western blot analysis confirms that Pb results in a significant decrease for VDAC. Decreases in VDAC expression could lead to an up-regulation of other cellular energy producing systems as a compensatory mechanism, and a Pb-induced increase in brain type creatine kinase is observed in auditory regions of the brainstem. In addition, comparative proteomic analysis shows that several proteins of the glycolytic pathway, the phosphocreatine circuit, and oxidative phosphorylation are also upregulated in response to developmental Pb exposure. Thus, Pb-induced decreases in VDAC could have a significant effect on the function of auditory neurons.